WAYS TO IMPROVE THE EFFICIENCY OF THE PROGAM-TARGETED OF INFRASTRUCTURE OBJECTS IN RUSSIA - A. V. Frolova (Модернизация, инновация, развитие, 2015)
The relevance of this article due to the fact that the current situation inRussiais complemented by the negative eff ects of market reforms in the economy, initiated economic sanctions that have been taken against our country. In view of this, for the eff ective fi nancing costs of the federal budget for the development of transport infrastructure is a very topical issues related to the targeted program planning. The study aims to study ways to improve the effi ciency of program fi nancing expenditures of the federal budget for the development of transport infrastructure. The results will contribute to solving urgent problems in the development of transport infrastructure, high technology and housing sectors.